Improving organizational effectiveness - Armstrong, Michael (Kogan page, 1994)
The major changes that have been affecting businesses in recent years have called for a large-scale reappraisal of the management of organizations and their individual staff members. Providing practical advice on the key elements that improve effectiveness, this study details a modern approach to human resource management that covers job design, the management of change, leadership skills, empowerment, team-building and productivity and quality management.